KAJIAN AKSIOLOGIS TRANSFORMASI DIGITAL PENDIDIKAN MELALUI PEMANFAATAN SMART TV DAN IFP DI SEKOLAH DASAR - Layara, Nikmah; Pujowati, Octalina Kus; Setyaningsih; Surachmi, Sri; Ratnasari, Yuni (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
The rapid advancement of digital technology has brought substantial changes to learning practices in elementary schools. Through the national digitalization program, the Indonesian government provides Smart TVs and Interactive Flat Panels (IFP) to enhance instructional quality and digital literacy, including in elementary schools across Rembang Regency. The integration of these devices not only transforms teaching methods but also introduces ethical and value-related challenges, particularly concerning moral responsibility, equity of access, and the humanistic dimension of learning. This study aims to analyze the effectiveness, value orientation, and ethical implications of Smart TV and IFP use based on an axiological perspective of the philosophy of science. Employing a descriptive qualitative approach with a case study design in five beneficiary schools, data were collected through classroom observations, in-depth interviews with teachers and principals, and document analysis. The findings indicate that the use of Smart TV and IFP: (1) increases student engagement and interaction, (2) supports teachers in delivering more engaging and contextual material, (3) enhances students’ motivation and interest, and (4) fosters teacher creativity in technology-based instruction. However, challenges remain, including disparities in teachers’ digital competence and technical limitations in schools. From an axiological standpoint, the success of digital transformation depends not only on the availability of devices but also on value awareness, ethical responsibility, and a commitment to using technology as a means of character formation and human development.